Analisis Kinerja Perusahaan: Peran Good Corporate Governance pada Industri Sektor Pariwisata Dan Transportasi di Era Pandemi - Anna Kania Widiatami (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
The tourism sector has a role as a contributor through the country's foreign exchange earnings in the Indonesian economy. From year to year there has been a significant increase in foreign tourist arrivals to tourist areas in Indonesia. However, when the Covid-19 pandemic hit Indonesia, it paralyzed almost all industries in Indonesia. This phenomenon affects the performance of companies, including the tourism industry. Company performance is a picture of company activities in using resources effectively and efficiently to achieve company goals. Good company performance is inseparable from the role of corporate governance or in other terms Good Corporate Governance. This study aims to examine the mechanism of Good Corporate Governance, namely gender diversity, the board of commissioners, and the audit committee on company performance. This study used a purposive sampling technique to obtain the number of samples was 114 samples from tourism and transportation sub-sector companies in 2019-2021. The data analysis technique of this study used multiple regression analysis, which was processed with the help of WarpPLS 8.0. The results of this study indicate that gender diversity, the board of commissioners, company size have no effect on company performance, while the audit committee has an effect on the performance of accommodation companies in the tourism and transportation subsector.